An insider's view on establishing an immovable property registration system in Albania - Sherko, Romeo; University of Wisconsin--Madison. Land Tenure Center.; Albania. Immovable Property Registration and Market Action Plan (Project). Project Management Unit. (Land Tenure Center, University of Wisconsin-Madison, 1997)
As will become clear in this article, the author's position shifts from pessimist to optimist as this writing progresses. The first section presents some of the difficulties that Albania is experiencing with respect to the immovable property registration system (IPRS) project (pessimist's position). The next section offers some of the advantages to be found in the Albanian system (optimist's position). The last section considers several plans used to deal with the problems; these programs are both tactical and strategic and, in my opinion, require careful coordination to resolve the difficulties encountered.
iii, 6 p.
Keywords: Land titles Registration and transfer Albania; Land use Information services Albania; Land administration Albania